Penanaman Jiwa Kewirausahaan dalam Peningkatan Life Skill Santri Pondok Pesantren Baitul Qona’ah di Mlandangan Pace Nganjuk - Nur Rulifatur Rohmah; Mohamad Mustafid Hamdi; Abdul Jalil Jawhari (Janaka, Jurnal Pengabdian Masyarakat, 2022)
Increasingly fierce competition in various fields of life requires everyone, especially the younger generation, to be able to create and innovate continuously. A generation that is smart, brave, critical, caring, optimistic and tough to compete with the younger generations of other nations. Santri as the younger generation who attend Islamic religious education at Islamic boarding schools need to prepare themselves to be able to seek opportunities and solve problems in everyday life with creative and innovative minds. With the hope that 1. Santri have an entrepreneurial spirit, 2. Santri can open jobs in the community, 3. Develop life skills of students. In this mentoring, we use several steps so that the mentoring program is as expected. The steps in assistance are as follows: Social analysis, Compilation of programs, Coordination, Implementation, Control. From the programs that have been planned and implemented, it can be seen that there are real changes in the form of increased understanding related to entrepreneurship and having guidelines that have been presented at seminars. Apart from that, the enthusiasm of the students in entrepreneurship has increased, so that the students will develop their life skills by establishing small businesses until they are successful.